General rules for preparing blood for laboratory testing - Sayfutdinova Z.A; Abdullayeva G.B; Xidoyatova M.D (Genius Journals, 2023)
Obtaining material for analysis Blood is taken from a vein Blood is taken from the finger Blood sampling from the wrist vein should be done with blood flow using a wide slotted cannula. The most common mistake in blood collection is the incorrect use of anticoagulant.
Keywords: Blood; analysis; material; vein